Konsep Higher Order Thinking Skills (HOTS) dalam Pemikiran Pendidikan Islam - Hidayatussaadah, Ita (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2021)
Islamic education must give birth to individuals who have positive behavior according to the goals of education itself. One figure of Islamic education thought argued that the purpose of education includes three aspects namely cognitive aspects which include the development of reason, such as intelligence, and power of thought; apective aspects include the development of the heart, such as the development of taste, heart and spirit and psychomotor aspects, namely physical development such as physical health and skills. These three aspects have a very close connection and attachment. By having good, critical and analytical reasoning, students will be able to find values ​​that internalize themselves, plunge into their hearts so as to produce attitudes and behaviors as a manifestation of the knowledge they have acquired. The ability to think critically and analytically requires a high level of reasoning known as Higher Order Thinking Skills (HOTS).